Polymorphisms in drug-resistant-related genes shared among drug-resistant and pan-susceptible strains of sequence type 10, Beijing family of Mycobacterium tuberculosis. Issue 1 (March 2015) - Regmi, Sanjib Mani; Coker, Olabisi Oluwabukola; Kulawonganunchai, Supasak; Tongsima, Sissades; Prammananan, Therdsak; Viratyosin, Wasna; Thaipisuttikul, Iyarit; Chaiprasert, Angkana
Abstract Mutations in genes involved in drug metabolism have been well-associated with drug resistance. Sequence analysis of known antimycobacterial drug-resistant genes is often used to predict resistance to antibiotics. However, some polymorphisms in such genes may serve a phylogenetic purpose rather than resistance to drugs. The Beijing family of Mycobacterium tuberculosis (MTB) is prevalent worldwide and has been associated with the emergence of multidrug resistance. Sequence type (ST) 10 of the Beijing family is the most predominant in countries like Peru, Taiwan and Thailand. A sequence analysis was performed of 81 previously reported drug-resistant associated genes in multidrug-resistant and pan-susceptible strains of the Beijing family sequence type 10 of MTB. This analysis revealed 10 synonymous and 12 nonsynonymous single nucleotide polymorphisms (SNPs) that are shared by all strains under study. One frameshift mutation was also observed to be common to all. These data might be useful in excluding some observed SNPs in drug-resistant-associated genes of MTB Beijing ST 10 when performing genotypic drug susceptibility assay.